2014
DOI: 10.1002/agr.21394
|View full text |Cite
|
Sign up to set email alerts
|

Association between Innovative Entrepreneurial Orientation, Absorptive Capacity, and Farm Business Performance

Abstract: A growing interest emerges with regard to how entrepreneurship and innovation can contribute to the success and well-being of the farmers. The main objective of the study is to develop and test a model, which emphasizes the relationship of trust and innovative entrepreneurial orientation on absorptive capacity in an agricultural context. This article examines also the effect of absorptive capacity on innovation as well as the connection of both innovative entrepreneurial orientation and innovation outcome on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 69 publications
7
71
2
6
Order By: Relevance
“…In accord with Li et al (2011), cooperation members' entrepreneurial orientation -reflected in their innovativeness, pro-activeness and risk taking-significantly determines the knowledge acquisition from inter-relationship activities between producer and distributer. This is consistent with the literature on both entrepreneurship and knowledge management, where scholars agree with the effects of knowledge acquired from external sources and firm's entrepreneurial orientation (Gellynck et al 2015). In fact, a company's management committee feels more confident taking entrepreneurial actions when it has more knowledge about the business opportunities or threads.…”
Section: Discussionsupporting
confidence: 78%
“…In accord with Li et al (2011), cooperation members' entrepreneurial orientation -reflected in their innovativeness, pro-activeness and risk taking-significantly determines the knowledge acquisition from inter-relationship activities between producer and distributer. This is consistent with the literature on both entrepreneurship and knowledge management, where scholars agree with the effects of knowledge acquired from external sources and firm's entrepreneurial orientation (Gellynck et al 2015). In fact, a company's management committee feels more confident taking entrepreneurial actions when it has more knowledge about the business opportunities or threads.…”
Section: Discussionsupporting
confidence: 78%
“…We started to make a profit and were even able to sell the product back to Japan after 5 years of losses' (M10). This result echoed those of previous studies (Gellynck et al, 2015;Liu et al, 2014), indicating that investment in product or process innovation can enhance product attractiveness, reduce production costs, and increase market potential.…”
Section: Innovations In Organizational Strategiessupporting
confidence: 76%
“…Liu, Kemp, Jongsma, Huang, Dons, and Omta (2014) further argued that integrative capabilities play a crucial role in innovation novelty, which enhances product superiority, and in improving functional capabilities and gaining market potential. In addition, Gellynck, Cárdenas, Pieniak, and Verbeke (2015) confirmed that trust and innovative entrepreneurial orientation influence farmers' absorptive capacity, and that innovative entrepreneurial orientation influences agribusiness performance.…”
Section: Internal Environmentmentioning
confidence: 50%
“…Studies in management literature [31][32][33] and agricultural economics [21,34,35] also examined adoption as a function of learning orientation. Different parts of production systems and of the environment in which they are embedded (e.g., the value chain, the market, the policy environment) need to develop simultaneously in order to enable innovation.…”
Section: Introductionmentioning
confidence: 99%